Michel Foucault e a história arqueológica - Bach, Augusto (Universidade Federal de São Carlos, 2006)
The main objective of this doctor degree thesis is to analyze the philosophical problems of Michel Foucault s archeological history presented in two of his major works: Madness and Civilization and The Order of Things. This last work, at the same time philosophical and related to historical science, has as its main goal (defined in its subtitle) to accomplish an archeology of the human sciences. The stretching of his investigation field to study the human sciences can be understood as a natural thematic progression of Foucault s research about the archeology of history. Since Madness and Civilization, Foucault has been always interested in showing how our culture sought to understand what was the fundamentally the other in man. In The Order of Things, taking as a starting-point the study of certain strategies that man used to comprehend himself, Foucault has constructed his archeological history stressing the discontinuities that ended up presenting our own culture as strange to us. It is about the philosophical problem of the historical discontinuities signalized by Foucault and its relation to a traditional, continued and dialectical history that this thesis will deal in its chapters, attempting to understand the philosophical position of this new way of writing history.
Keywords: Filosofia francesa; Foucault, Michel, 1926-1984; Biografia - filósofo; Literatura francesa; Archeology; History; Philosophy; Literature; CIENCIAS HUMANAS::FILOSOFIA